PROPAGANDA OF HEALTHY LIGHTS AMONG YOUTH (American Journal of Pedagogical and Educational Research, 2023)
in recent years, attention has been paid to the healthy lifestyle of the younger generation. In this paper, the project "Healthy nation - the strength of the state", developed in the framework of the grant of the Termez Office for the promotion of components of a healthy lifestyle in educational institutions is presented. Within the framework of the project, the stages of introducing the foundations of a healthy lifestyle in higher and secondary educational institutions were developed. The project implementation was successful, goals and tasks were fulfilled, problems were identified.